Digital Transformation Socialization in Supporting the Micro, Small Medium Enterprise (MSMEs) of Bulak Village - Maryatul Kibtyah; Salwa Najla Jinan; Siti Nur Rohmah; Nurlaela Annajmi; Yanwar Affandhy (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
MSMEs have an important role in the village economy. They create jobs, contribute to infrastructure development and increase employment income. MSMEs are also able to take advantage of local potential, such as natural resources and cultural wisdom, to develop products that are relevant to the needs of the local community. MSMEs play a role in distributing development results. Digital transformation is a global phenomenon that refers to a massive shift from analog to digital systems and processes. This is a fundamental change spurred by the rapid development of information and communication technology. Bulak Village is a village located in Kendal Regency, Central Java. This village has the potential of MSMEs that can be developed through the sustainability of the digital era. However, many Bulak residents still do not understand how to use technology as a facilitator of their business. It is necessary to socialize about digital transformation for MSMEs owner in Bulak village so that MSMEs become wider in marketing their products. The Method are The method used in this socialization activity is an offline seminar method involving various elements Starting from academics, thematic village activists, MSMEs actors in the village and the community common. The seminar participants who attended were very enthusiastic in listening to the material presented by the speakers. After delivering the material, some participantsgave questions that were still confused regarding the use of digital platforms to the speakers. This activity was held by a team of students from Walisogo State University's real work lecture.